Fast Fluorine-18 labeling and preclinical evaluation of novel Mucin1 and its Folate hybrid peptide conjugate for targeting breast carcinoma - I. Al Jammaz; B. Al-Otaibi; Y. Al-Malki; A. Abousekhrah; S. M. Okarvi (SpringerOpen, 2021)
Abstract Background There is a need to develop new and more potent radiofluorinated peptide and their hybrid conjugates for multiple-receptors targeting properties that overexpress on many cancers. Methods We have synthesized MUC1-[18F] SFB and MUC1-FA-[18F] SFB hybrid conjugates using a convenient and one-step nucleophilic displacement reaction. In vitro cell binding and in vivo evaluation in animals were performed to determine the potential of these radiolabeled compounds. Results Radiochemical yields for MUC1-[18F] SFB and MUC1-FA-[18F] SFB conjugates were greater than 70% in less than 30 min synthesis time. Radiochemical purities were greater than 97% without HPLC purification, which makes these approaches amenable to automation. In vitro studies on MCF7 breast cancer cells showed that the significant amounts of the radiofluorinated conjugates were associated with cell fractions and held good affinity and specificity for MCF7 cells. In vivo characterization in Balb/c mice revealed rapid blood clearance with excretion predominantly by urinary as well as hepatobiliary systems for MUC1-[18F] SFB and MUC1-FA-[18F] SFB, respectively. Biodistribution in SCID mice bearing MCF7 xenografts, demonstrated excellent tumor uptake (12% ID/g) and favorable kinetics for MUC1-FA-[18F] SFB over MUC1-[18F]SFB. The tumor uptake was blocked by the excess co-injection of cold peptides suggesting the receptor-mediated process. Conclusion Initial PET/CT imaging of SCID mice with MCF7 xenografts, confirmed these observations. These results demonstrate that MUC1-FA-[18F] SFB may be a useful PET imaging probe for breast cancer detection and monitoring tumor response to the treatment.